Improving Students Motivation and Engagement Through a Competitive Trivia Game - Jackson Jackson; Leil Badrah Zakti (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
English becoming an international language has made it became a worldwide necessity to teach and learn English. One of the most important skill is speaking and in this study the author has discovered the problem that students do not participate in class enough in which they do not speak English much and resulted in a mediocre speaking skill. A solution was proposed which is game-based learning (GBL) and specifically a competitive style game-based learning. Multiple studies has suggested that GBL has a strong impact on students motivation and engagement in class and also suggested that having competition can also further motivate and increase their cognitive skills in a learning environment. Multiple GBL research has taken place but it is a rare occurrence for combining competition into the fray and observing the effects for this multiple treatment. The findings suggested that both GBL and competition does indeed have a positive impact towards the participant’s motivation and engagement. A Classroom Action Research (CAR) research design was used in this study following up with a mixed method design afterwards. The results of the pre-test and post-test confirms to have an improvement on their scores and the results of the questionnaire and interview has also confirmed that the participants does feels more motivated and engaged than